THE CLOUD IMAGE IN THE HISTORY OF THE TEXT OF M.A. BULGAKOV’S NOVEL “MASTER AND MARGARITA” (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-2-113-129The focus is on the formation of the cloud image in the history of the text of M.A. Bulgakov’s novel “The Master and Margarita”. We try to understand the author’s plan based on the textual analysis of the novel. Having considered the cloud image in the Ershalaim and Moscow spaces of the novel, the author of the article concludes that this image belongs to Woland’s world. The history of the text demonstrates that the cloud image performs several functions: warning and striving to stop the heroes from making a mistake; purification, which must be passed before the start of a new life; funds connecting the Ershalaim and Moscow spaces of the novel as a sign of “the world catastrophe”.Key words: creative history, textual analysis, М.А. Bulgakov, “The Master and Margarita”, cloud image